Unraveling Philosophical Justice in Judges’ Decisions on Marital Property Disputes: A Jurimetric Analysis - Julir, Nenan; Jayusaman, Jayusaman; Khairunnisa, Khairunnisa; Humaidulloh, Humaidulloh; Ulfaturrosydah, Ai; Yelpi, Agusti (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
This study is aimed at analyzing the Jurimetrcs of the decision Number: 0420/Pdt.G/2017/PA.Mt dealing with marital property disputes suspected of failing to fulfill the sense of justice of the disputing couple. The method used in this study is qualitative content analysis, analyzing documents and texts of court judge decisions. Qualitative content analysis identifies, processes, and describes the judge's decision, then relates it to society's social and cultural context. The analysis of this study revealed that the judge's decision was only guided by the Compilation of Islamic Law article 97; if a husband and wife divorced, each of them would get half of the marital property, without considering the wife's position as the main breadwinner and the portion of duties and obligations in the family. Jurimetric analysis of the decision is considered to create a sense of justice. In the context of distributing marital property in Indonesia, Jurimetrcs can assist judges in determining the value of the share of joint property for each husband and wife after an equitable divorce. Penelitian ini bertujuan untuk menganalisis jurimetri terhadap putusan Nomor: 0420/Pdt.G/2017/PA.Mt tentang sengketa harta bersama yang diduga belum memenuhi rasa keadilan dari para pihak yang bersengketa. Metode yang digunakan dalam penelitian ini adalah metode analisis isi kualitatif, yakni menganalisis dokumen dan teks putusan hakim pengadilan. Analisis isi kualitatif digunakan untuk mengidentifikasi, mengolah, dan menguraikan putusan hakim yang kemudian menghubungkannya dengan konteks sosial dan budaya masyarakat. Hasil analisis penelitian ini mengungkapkan bahawa putusan hakim hanya berpedoman pada Kompilasi Hukum Islam pasal 97, yakni jika pasangan suami istri bercerai, masing-masing akan mendapatkan seperdua dari harta bersama. Tanpa mempertimbangkan posisi istri sebagai pencari nafkah utama maupun porsi tugas dan kewajiban dalam keluarga. Analisis jurimetri terhadap putusan tersebut dinilai dapat mewujudkan rasa keadilan. Dalam konteks pembagian harta bersama di Indonesia, jurimetri dapat membantu hakim dalam menentukan nilai bagian harta bersama pada masing-masing suami dan istri setelah terjadi perceraian yang berkeadilan.